2014 IEEE International Conference on Communications (ICC) 2014
DOI: 10.1109/icc.2014.6884089
|View full text |Cite
|
Sign up to set email alerts
|

28 GHz and 73 GHz signal outage study for millimeter wave cellular and backhaul communications

Abstract: This paper presents millimeter wave propagation measurements in New York City and an analysis of signal outage at 28 and 73 GHz using similar spread spectrum sliding correlator channel sounders that employed high gain, directional steerable antennas (24.5 dBi gain antennas at 28 GHz and 27 dBi gain antennas at 73 GHz) at both the transmitter and receiver. Three identical transmitter locations were used for both the 28 and 73 GHz campaigns, while the 73 GHz campaign included two new TX locations. The 28 GHz cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Consequently, the coverage range of a millimeter wave base station is dramatically limited to only a few hundred meters, even with high-gain (more than 50 dBi at transmitter and receiver combined) antennas used at both the transmitter and receiver. An outage study from the measurement campaign in New York City showed that the maximum cell radius is 200 meters at 28 and 73 GHz, and the major blockage effect is caused by the dense buildings in urban environments [61].…”
Section: Propagation Characterizationmentioning
confidence: 99%
“…Consequently, the coverage range of a millimeter wave base station is dramatically limited to only a few hundred meters, even with high-gain (more than 50 dBi at transmitter and receiver combined) antennas used at both the transmitter and receiver. An outage study from the measurement campaign in New York City showed that the maximum cell radius is 200 meters at 28 and 73 GHz, and the major blockage effect is caused by the dense buildings in urban environments [61].…”
Section: Propagation Characterizationmentioning
confidence: 99%
“…The second simulation campaign is designed to study and compare the performance of X-TCP against that of other congestion control algorithms after an extended outage event, i.e., after a TCP retransmission timeout is triggered. These events are unlikely in a scenario with a dense deployment of mmWave base stations, because the UE would handover to a different eNB with a very high probability [23], but they may happen nonetheless [24], thus it is important to study the behavior of transport protocols also in these scenarios. In particular, when an RTO is triggered, TCP restarts from slow start with a congestion window set to MSS bytes.…”
Section: Evaluation In Blockage Scenariosmentioning
confidence: 99%
“…The millimeter-wave band answers some challenges related to the requirements of broadband frequency usage. Millimeter waves still have sufficient bandwidth for the upcoming wireless technology implementation [11], where .28 GHz is one of the frequency candidates for the implementation of 5G network technology [12,13,14].…”
Section: Introductionmentioning
confidence: 99%